The Role of Social Media in Improving Woven Blanket Industry Business Performance in Garut Regency - Maulani, Galih Abdul Fatah (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2019)
The use of social media is one of strategic alternative in a business. It plays a crucial role in developing business community networking and enhances business performance. This research was designated to examine the effect of social media in fostering MSME business performance. This quantitative study involved 42 woven blanket MSMEs in Cintarasa Village, Samarang District, Garut Regency, Indonesia. The data analysis was performed through PLS-SEM. The result discovered that social media has a significant effect and strongly affect Garutian woven blanket business performance. This social media can be optimally utilized by taking certain criteria into account.